An inexpensive, simple and effective method of genome DNA fragmentation for NGS libraries. (11th August 2021) - Kechin, Andrey; Boldyreva, Darya; Borobova, Viktoriya; Boyarskikh, Ulyana; Scherbak, Sergey; Apalko, Svetlana; Makarova, Maria; Mosyakin, Nikolay; Kaftyreva, Lidia; Filipenko, Maxim
Abstract: Next-generation sequencing (NGS)-library preparation for whole-genome sequencing (WGS) starts with DNA fragmentation, and sonication is a physical approach used most often due to its simplicity and reproducibility. However, the commercially available Covaris instrument has a high price for both the device and consumables. Here, we describe our in-house method of DNA shearing by sonication with small (100–600 µm) glass beads and an ultrasonic bath. The fragmentation conditions were optimized for the bacterial WGS with ∼550-bp fragment size (the ultrasonic bath water temperature 5–10°C, glass beads 0.06 g, the fragmentation time 50 s) and for human DNA with ∼250 bp (fragmentation with the same parameters for 4 min). Fragmentation results were compared with the Covaris instrument for preparing several bacterial NGS libraries for Illumina NGS platforms by several characteristics. We obtained close mean fragment lengths (523–623 versus 480–646), similar mono- and dinucleotide specificity of shearing, and comparable indicators of read alignment and de novo assembly for both methods. Thus, the described method is a new fast, and effective DNA fragmentation approach that can be used in different WGS applications. Graphical Abstract: